Nonmonotonic rate-dependent adhesion of hydrogels - Dongjing He; Jiahe Huang; Yuhang Hu (Proceedings of the National Academy of Sciences, 2026)
Hydrogel adhesion underlies a wide range of biological and engineering functions, yet its rate dependence remains poorly understood. Classical adhesive systems exhibit a monotonic increase in adhesion strength with separation rate, a behavior attributed to bond stress relaxation. Here, we show that hydrogels fundamentally deviate from this paradigm. Using atomic force microscopy-based indentation over six orders of magnitude in retraction rate, we find that the pull-off force first decreases and then increases, revealing a distinctly nonmonotonic rate dependence in hydrogels. To explain this behavior, we develop a quantitative model that couples the deformation of the hydrogel with a rate-dependent traction carried by interfacial bonds with distinct association and dissociation kinetics. The model reproduces the full pull-off force spectrum exhibiting the nonmonotonic behavior and predicts the evolution of the contact radius during detachment. In situ confocal microscopy measurements of contact-area dynamics confirm these predictions, providing independent validation of the kinetic mechanism. Together, the experiments and theory reveal that hydrogel adhesion is governed by a competition between time-dependent bond formation, which strengthens adhesion at slow rates, and limited bond relaxation, which enhances traction at fast rates. This interplay produces a broad intermediate regime in which reduced contact time suppresses bond buildup and weakens adhesion. Our findings identify a previously unrecognized adhesion regime in polymeric materials and provide a unified framework for understanding and designing hydrogel interfaces whose performance depends sensitively on rate, contact history, and interfacial bonding kinetics.